Adrenal insufficiency - causes and laboratory diagnosis - Brutvan, Tomas; Jezkova, Jana; Kotasova, Marcela; Krsek, Michal (Biomedical papers, 2025)
Adrenal insufficiency (AI) manifests as a clinical syndrome arising from either the direct impairment of adrenal glands, leading to primary AI characterized by deficiencies in glucocorticoids and mineralocorticoids, or adrenal cortex atrophy due to diminished adrenocorticotropic hormone (ACTH) stimulation, a consequence of hypothalamic and/or pituitary damage, resulting in secondary AI. The diagnosis of AI is based on clinical assessment and biochemical tests, including basal hormone level measurements and stimulation tests. In evaluating the results of laboratory tests, it is necessary to consider factors that may influence both pre-analytical and analytical phases, as well as the chosen methodology. Correct diagnosis of adrenal insufficiency and timely initiation of suitable replacement therapy are paramount. These steps are crucial not only for managing the condition but also to avert potentially life-threatening adrenal crises.
Keywords: adrenal insufficiency; cortisol; adrenocorticotropic hormone; stimulation test